Semantic Mining Technologies for Multimedia Databases (Premier Reference Source) - Tao, Dacheng (Infomation Science Reference, 2011)
Multimedia searching and management have become popular due to demanding applications and competition among companies. Despite the increase in interest, there is no existing book covering basic knowledge on state-of-the-art techniques within the field.